G-protein Coupled Receptor 30 Interacts with Receptor Activity Modifying Protein 3 and Confers Sex-Dependent Cardioprotection - Lenhart, Patricia M. (2013)
Receptor activity modifying protein 3 (RAMP3) is a single pass transmembrane protein known to interact with and affect the trafficking of several G-protein coupled receptors (GPCRs). We sought to determine whether RAMP3 interacts with G-protein coupled receptor 30 (GPR30), also known as G-protein estrogen receptor 1 (GPER1). GPR30 is a GPCR that binds estradiol and has important roles in cardiovascular and endocrine physiology. Utilizing bioluminescence resonance energy transfer titration studies, co-immunoprecipitation, and confocal microscopy, we show that GPR30 and RAMP3 interact. Furthermore, the presence of GPR30 leads to increased expression of RAMP3 at the plasma membrane in HEK293 cells. In vivo, there are marked sex differences in the subcellular localization of GPR30 in cardiac cells, and the hearts of Ramp3(−/−) mice also show signs of GPR30 mislocalization. To determine whether this interaction might play a role in cardiovascular disease, we treated Ramp3(+/+) and Ramp3(−/−) mice on a heart disease-prone genetic background with G-1, a specific agonist for GPR30. Importantly, this in vivo activation of GPR30 resulted in a significant reduction in cardiac hypertrophy and perivascular fibrosis that is both RAMP3- and sex-dependent. Our results demonstrate that GPR30-RAMP3 interaction has functional consequences on the localization of these proteins both in vitro and in vivo, and that RAMP3 is required for GPR30-mediated cardioprotection.